Pembuatan Konten Pemasaran Bagi Pengrajin Batik di Desa Jarum Kecamatan Bayat Kabupaten Klaten - Nuryakin; Firman Pribadi (JURNAL ABDIMAS SERAWAI, 2021)
The emergence of social media that has been widely adopted by companies today has provided a change in the direction and business strategy and communication patterns run by the company. Changes in strategy and communication patterns are also carried out by the SME sector. The SME sector, which a few years ago still adopted strategies and forms of direct communication, has now also adapted to using social media. Social media has also influenced the choice of the company's strategy in establishing relationships with its customers. Even SMEs must also change theirstrategy in dealing with the emergence of social media today, including in marketing activities. The importance of building SME relationships and their relationships has been carried out with the concept and seeking social interaction through social networks using Facebook, Instagram and other social media. The reputation of SMEs will be known by the public. One form is in batik SMEs who try to market their products online through marketing content. This service activity is a Community Partnership Program (PKM) which is carried out on batik SMEs in the village of Jarum, Bayat District, Klaten Regency. The output of this PKM activity is the creation of marketing content for batik products produced from batik production activities such as batik cloth, handicrafts, toys and several other accessories produced from the batik process. Marketing content for these products is made and then uploaded on YouTube so that it is easily recognized by customers in a wide range.